2013
DOI: 10.1002/cbin.10181
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐based injectable hydrogel as a promising in situ forming scaffold for cartilage tissue engineering

Abstract: Chitosan-beta glycerophosphate-hydroxyethyl cellulose (CH-GP-HEC) is a biocompatible and biodegradable scaffold exhibiting a sol-gel transition at 37°C. Chondrogenic factors or mesenchymal stem cells (MSCs) can be included in the CH-GP-HEC, and injected into the site of injury to fill the cartilage tissue defects with minimal invasion and pain. The possible impact of the injectable CH-GP-HEC on the viability of the encapsulated MSCs was assessed by propidium iodide-fluorescein diacetate staining. Proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 71 publications
(228 reference statements)
2
75
0
1
Order By: Relevance
“…92,93,94, 95 Recently, chitosan has become increasingly attractive as an injectable hydrogel for cartilage repair, owing to its structural similarity to cartilage glycosaminoglycan. 43,93,96 Chen et al 48 have fabricated a tough chitosan–gelatin hydrogel via an in situ precipitation method. This in situ formed hydrogel exhibits improved mechanical properties, and is biodegradable and biocompatible.…”
Section: Injectable Hydrogels Prepared With Different Biomaterialsmentioning
confidence: 99%
“…92,93,94, 95 Recently, chitosan has become increasingly attractive as an injectable hydrogel for cartilage repair, owing to its structural similarity to cartilage glycosaminoglycan. 43,93,96 Chen et al 48 have fabricated a tough chitosan–gelatin hydrogel via an in situ precipitation method. This in situ formed hydrogel exhibits improved mechanical properties, and is biodegradable and biocompatible.…”
Section: Injectable Hydrogels Prepared With Different Biomaterialsmentioning
confidence: 99%
“…21 Chitosan is structurally analogous to GAGs, and HA is a major component of the ECM in the NP. 10,12,14 Hydroxyl groups in HA can cross-link with amino groups in CS. CS when combined with glycerol phosphate and HA can undergo a sol-gel transition at 37°C by covalent crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another suitable candidate for cartilage and NP tissue repair is chitosan. Chitosan is structurally analogous to GAGs, 14 and is also nontoxic, water soluble, biodegradable, biocompatible and displays anti-bacterial properties. Chitosan has been investigated extensively for drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Another chitosan-β-glycerophosphate-hydroxy-ethyl cellulose (CH-GP-HEC) scaffold owns biocompatible, biodegradable and cytocompatible properties that could make a transition from sol to gel at 37 ℃. Naderi-Meshkin et al [31] found that TGF-β3 could induce the incorporated human mesenchymal stem cells (hMSCs) into chondrocytes. MSCs showed excellent survival and proliferative rates within CH-GP-HEC hydrogel during 28 d investigation, which indicate their good cytocompatibility.…”
Section: Alginatementioning
confidence: 99%